On the Second-Order Statistics of Correlated Cascaded Rayleigh Fading Channels. (26th July 2012) - Chau, Yawgeng A.; Huang, Karl Y.-T.
Abstract : The second-order statistics of two correlated cascaded (double) Rayleigh fading channels are analyzed, where different relevant second-order cross-correlation functions of in-phase and quadrature components of the cascaded Rayleigh channels are derived. The level crossing rate (LCR) and average fade duration (AFD) of the cascaded channels are evaluated, and a single-integral form of the LCR is derived. Numerical results of the LCR and AFD are presented, and the effect of the correlation is illustrated.